A meta-analysis of the acute and chronic effects of exercise training on Paraoxonase-1 (PON1) - Taylor, James Kyle (2020)
Purpose: Determine the acute and chronic effects of exercise training on PON1 concentration and activity. Methods: A literature search was performed in English and Spanish languages using 16 electronic databases and the keywords “PON1”, “exercise”, “paraoxonase”, “paraoxonase-1”, “paraoxonase 1”, “aerobic”, “resistance”, “training”, and “concurrent”. Experimental studies in adults 18 years of age and older were included. Dual selection and data abstraction were conducted. Results were pooled using the random-effects model. Effect sizes (ES) were computed and two-tailed alpha values <0.05 and non-overlapping 95% confidence intervals (95%CI) were considered statistically significant. Statistical heterogeneity (Q) and inconsistency (I2) were examined as well as small-study effects using the Doi plot and LFK index. Results: Seventeen studies representing 360 participants met the criteria for inclusion. The acute effects of exercise on PON1 concentration were trivial and non-significant (ES = -0.03, 95%CI = -0.39 to 0.34, p>0.05), heterogeneous (Q = 17.22, p=0.05), moderately inconsistent (I2 = 48%), with minor asymmetry (LFK index = 1.34). The chronic effects of exercise on PON1 concentration were also trivial and non-significant (ES = -0.04, 95%CI = -0.53 to 0.45, p>0.05), homogenous (Q = 0.85, p=0.65), displayed low inconsistency (I2 = 0%), and minor asymmetry (LFK index = -1.14). The acute effects of exercise on PON1 activity were trivial and non-significant (ES = 0.11, 95%CI = -0.02 to 0.24, p>0.05), homogenous (Q = 18.58, p=0.85), showed low inconsistency (I2 = 0%), and no asymmetry (LFK index = 0.82). The chronic effects of exercise on PON1 activity were small but significant (ES = 0.39, 95%CI = 0.01 to 0.77, p<0.05), homogenous (Q = 6.43, p = 0.17), moderately inconsistent (I2 = 38%), with no asymmetry (LFK index = 0.94). Conclusion: Exercise training, overall, exerted a trivial effect on PON1 while chronic exercise had a small but more pronounced effect on PON1 activity. Additional research is needed before any firm conclusions can be drawn.